COMPONENTS OF PROJECT-BASED EDUCATION: INCREASING STUDENT ENGAGEMENT IN THE LEARNING PROCESS - Febrinal, Dian; S, Rinny; Rahmawati, Aulia; Amra, Abhanda (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
This study aims to analyze the impact of Project-Based Learning (PBL) on the engagement and motivation of Junior High School students. (SMP). PBL is a learning approach that encourages students to work on projects relevant to the real world, thereby enhancing motivation and 21st-century skills, such as collaboration and problem-solving. This research uses a quantitative method with a survey approach through questionnaires given to eighth-grade students in two schools in Sijunjung, selected using purposive sampling technique. Data analysis was conducted using SPSS software, with a paired t-test to see the significant difference between the pretest and posttest. The research results show that PBL significantly increases students' motivation, participation, and satisfaction with the learning process. Questionnaire scores on scales 4 and 5 indicate an increase in students' motivation and engagement. Statistical analysis shows an increase in the average student score from 64.5 (pretest) to 77.5 (posttest) with a p-value < 0.05 and an effect size of 0.8, indicating a significant and large impact. This research concludes that PBL has a positive impact on student learning outcomes, particularly in enhancing critical thinking skills, collaboration, and learning motivation.